Development and validation of a social skills assessment tool for Vietnamese preschool children aged 5–6 - Nguyen Thieu Da Huong; Tran Thanh Nam; Dinh Thi Kim Thoa (Technium Social Sciences Journal, 2026)
The development and validation of social skills (SS) assessment tools are pivotal for evidence-based early childhood education, particularly for children aged 5–6—a critical transition period from preschool to primary school. However, Vietnam currently lacks systematically developed and standardized SS assessment batteries that align with children’s developmental characteristics and the domestic socio-cultural-educational context. This study aims to develop the SSIS scale by Gresham & Elliott (2008) and validate a social skills assessment toolkit for 5–6-year-old children in Vietnam – KNXH5T based on Classical Test Theory. The research was conducted using a quantitative design on a sample of 335 children aged 5–6 at 10 preschools in Hanoi. Analytical results identified the SS structure as comprising five component skills: communication, cooperation and participation, self-control and responsibility, and empathy. The KNXH5T toolkit consists of rating scales with rubrics for teachers and parents, along with direct situational testing tasks for children. Psychometric analyses using R-Studio software, including EFA, CFA, and Spearman correlations, showed that the toolkit has a clear factor structure, high reliability, and satisfactory measurement validity. Evaluation results indicated that children’s SS reached a "Good" level, with differences observed based on region and gender, while birth month did not significantly influence the results. This research contributes a scientifically grounded assessment tool with high practical application value for Vietnamese early childhood education.